Understory vegetation cover across a post-fire tree density gradient in far northeastern Siberia, 2016-2017 - Heather D. Alexander (Arctic Data Center, 2018)
In Siberian larch forests, tree density has multiple consequences for both above- and belowground carbon (C) pools within trees and soils as stands mature, but tree density could also influence understory vegetation cover and associated C pools. The primary objective of this study was to determine how fire-driven changes in tree density affect understory vegetation as stands mature within Cajander larch dominated forests of far northeastern Siberia.